Trace metals in mangrove seedlings: role of iron plaque formation - Machado, Wilson Thadeu Valle (2005)
Metal-rich mineral deposits on the roots of aquatic plants, denominated iron plaques, may moderate the uptake of essential, but potentially toxic metals by roots. We investigated the iron plaque formation on the fine, nutritive roots of mangrove seedlings growing in contrasting environments (oxidizing sand flat sediments and reducing mangrove forest sediments) in southeast Brazil. The results indicate that Avicennia schaueriana, Laguncularia racemosa, and Rhizophora mangle seedlings developed an efficient exclusion of Fe, Mn, and Zn through iron plaque formation. This process seems to be influenced substantially by speciesspecific responses to environmental conditions. While Fe and Zn translocation to leaves appear to be suppressed by accumulation within root tissues, this did not appear to occur for Mn, suggesting that Mn trapping in rhizosphere sediments and iron plaque formation are the main mechanisms responsible for the Mn exclusion from the organism level. In addition to factors well recognized as affecting mangrove seedling development (e.g., salinity stress and nutrient availability), the mediation of trace metal uptake by iron plaque formation possibly contribute to determine the seedling adaptability to waterlogged conditions.